Hearing impairment as an unusual presenting sign of Cryptococcus gattii meningoencephalitis - Gong, Sophie (BMJ Case Rep, 2021)
Hearing loss is an unusual presenting feature of Cryptococcus gattii meningoencephalitis. Two cases of HIV-negative patients who presented with hearing loss are discussed and a literature review of published cases was conducted. Possible mechanisms for hearing loss with C. gattii infection are explored. This case series aims to raise awareness among clinicians that hearing loss can be a concerning feature in patients with persistent headache necessitating further investigation.